Legal Measures for the Conservation of the Historic District: A Case Study of the Thap Thiang Historical District, Trang Province - Tipmontien, Chanida (Huachiew Chalermprakiet Law Journal, 2022)
The objective of this research was to study the legal measures related to the conservation of the historic district by studying the guidelines in the conservation of historic district from Japan’s legal measure. The point was to improve Thailand’s legal measures in an appropriate way to protect the historic district. According to the study, Thailand’s current legal measures were emphasized in conservation only the archaeological sites and government buildings, the specific building that was not inhabited by humans. However, the historic district was different from a desolated archaeological site. The historic district was populated by human’s lifestyles and contained styles of architecture that changed from time to time, altogether with dynamic movement. Besides, almost all of the buildings in the historic district were private buildings. Hence, to proceed conservation of the historic district efficiently, the buildings are ought to be separated into groups of buildings or a targeted district to put a limit on conservation. Additionally, rather than decreasing the compulsory measures, it was better to increase persuasive measures of the building’s owners to cooperate in building’s maintenance and conservation.